3D Independent Actuators Control Based On A Proportional Derivative Active Force Control - Pitowarno, Endra; Kamarudin, Kamarudin; Dewanto, R. Sanggar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
Crude palm oil has a high free fattThis paper presents a control method for 3D independent actuators using PDAFC (Proportional Derivative Active Force Control). PD is used to stabilize the actuators, where as AFC is used to reject disturbance uncertainty by estimating disturbance torque value of actuator. Simulation result shows that PDAFC can minimize disturbance uncertainly effect. To test the performances of a control system actuator given disorder constant and sine. To research it uses cube as an actuator. when give the actuators disturbance with the constant value of 45, to achieve setpoint actuators takes 1 second. This condition is in all actuators whether it was the yaw, pitch and roll. When give the actuators disturbance with the sine, to achieve setpoint actuators takes 1.25 second. This condition is in all actuators whether it was the yaw, pitch and roll.